2005
DOI: 10.1529/biophysj.104.045633
|View full text |Cite
|
Sign up to set email alerts
|

The Elementary Mass Action Rate Constants of P-gp Transport for a Confluent Monolayer of MDCKII-hMDR1 Cells

Abstract: The human multi-drug resistance membrane transporter, P-glycoprotein, or P-gp, has been extensively studied due to its importance to human health and disease. Thus far, the kinetic analysis of P-gp transport has been limited to steady-state Michaelis-Menten approaches or to compartmental models, neither of which can prove molecular mechanisms. Determination of the elementary kinetic rate constants of transport will be essential to understanding how P-gp works. The experimental system we use is a confluent mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
168
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(181 citation statements)
references
References 66 publications
9
168
3
1
Order By: Relevance
“…MATLAB fminsearch minimizes the coefficient of variation between the data and the simulated curves. Further details can be found in Tran et al (2005) and Bentz et al (2005).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…MATLAB fminsearch minimizes the coefficient of variation between the data and the simulated curves. Further details can be found in Tran et al (2005) and Bentz et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…Polarized confluent cell monolayers overexpressing P-gp have been used extensively as a model system to study P-gp transport mechanisms and to assess the risk of P-gp-mediated drug-drug interactions (Tang et al, 2002;Rautio et al, 2006;Bartholomé et al, 2007;Korjamo et al, 2007). Using the polarized Madin-Darby canine kidney II cell line that overexpresses human MDR1 (MDCKII-hMDR1) confluent cell monolayer, which overexpresses human P-gp in the apical plasma membrane and a detailed mass action analysis of P-gp efflux kinetics, we have been able to answer several fundamental questions about P-gp function Tran et al, 2005;Acharya et al, 2006). With P-gp as the only transporter in the kinetic model, we have found that amprenavir and quinidine were well fitted, whereas loperamide showed more efflux than could be explained by just P-gp (Tran Article, publication date, and citation information can be found at http://dmd.aspetjournals.org.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[196] The ongoing transgression of Michaelis-Menten kinetics for determining kinetic constants for efflux transporters and the difficulties in estimating the enterocytic concentration has been recognized by several groups that have attempted to derive Ki and Km values from more or less complex three-compartment models and simulation models. [30,189,190,[196][197][198][199] However, a thorough validation of these models is still lacking and it is outside the scope of this review to further address these models. As emphasized by Tachibana et al [193] , there is a need of standardizing both the in-vitro methods and the method used for the Ki/IC50 calculations.…”
Section: Limitations Of In-vitro Determined Kinetic Parameters For Trmentioning
confidence: 99%